Modeling the human mind as an information processor :|a Heideggerian critique - Alpagut, Emre. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
Research efforts seeking to construct a scientific study of mind became institutionalized as cognitive science after World War II. These research efforts were inspired by the technological developments of that era in three domains: cybernetics, Turing computation and information theory. Although originally designed for engineering applications in controlled environments, these technological frameworks and concepts were adopted by researchers to give an account of the human mind. Consequently, “mind is an information processor” emerged as the central premise of cognitive science. Despite this information-related premise, cognitive science lacks a rigorous definition of the term information. Furthermore, the information processor approach necessitates a conception of mind consisting of discrete, enumerable constituents whose relations are well-defined. Such a conception recognizes mental capabilities insofar as they can be portrayed as a computational process and explains away metaphysical conceptualizations of subjectivity by portraying mental processes as emergent effects produced from complex interactions among simple entities. This relationship between technology and science during cognitive science’s proliferation can be examined from a Heideggerian perspective. Heidegger conceptualizes technology as a mode of being and argues that technology uses science to fulfill its essence. The technological mode of being conceives all entities as standing reserve (Bestand), resources to be extracted and ordered. Cognitive science models mental processes as computational operations and thereby represents the human mind as an orderable resource.
Keywords: Human behavior models.; Cognitive science.; Cognitive neuroscience.